Numerical Investigations of Nano-fluid Flow in Square Porous Cavity: Buongiornoâs Mathematical Model - Zafar, M. (Springer Science and Business Media B.V., 2021)
Buongiornoâs mathematical Nanofluid model is used to investigate the steady-state natural convection process and heat generation in a two-dimensional (2D) porous square cavity dripped in Nanofluid. The problem focuses on the dimensionless momentum equations, energy equations, and nanoparticle concentration. The Rayleigh number, Lewis number, Darcy number, buoyancy-ratio parameter, Brownian motion parameter, thermophoresis parameter, Prandtl number, and aspect ratio are all investigated in this paper. The governing system of partial differential equations was discretized using the finite volume method (FVM), the continuity and momentum equations were discretized using the SIMPLE algorithm, and the generated algebraic equations are solved iteratively. The generated algorithm has been evaluated in terms of Nusselt number and Sherwood number by comparing it to earlier published work, and the findings are in good agreement. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.